La noche de las encomiendas: Condiciones y contingencias para el alzamiento general en la Gobernación del Tucumán (1629-1631) - Laura Quiroga (Nuevo mundo - Mundos Nuevos, 2021)
This article proposes an analysis of the general uprising of 1630 that took place at the high grounds of the Governance of Tucumán. It is guided by two aims: a) a revision of the theoretical categories of domination and resistance applied to the study of Calchaquí wars during the 16th and 17th centuries; b) to reconstruct the tensions of the encomendero (grant holder) estate to achieve the benefit of the encomienda. It suggests these internal confrontations became the structure and condition for the outbreak of rebellions that looked for – and managed to achieve in many occasions – the depopulation of Spanish cities established in their territories. In order to achieve this, we analyze the politics of governor Albornoz regarding the central conflict of the encomendero estate from the cities of Tucumán: the fight over access to work of the encomienda Natives that forced the Calchaquí resistance. Without abandoning nor ignoring war accounts, the focus of this article aims to search the internal political tensions of colonial order that caused the Indigenous revolt; that is to say, in which way the structural tensions of the society are settled through the general uprising of 1630.